Synthesis, structure and density functional theory (DFT) study of a rhenium(I) pyridylpyrazol complex as a potential photocatalyst for CO2 reduction - Mark-Lee, Wun Fui; Chong, Yan Yi; Law, Kung Pui; Ishak Ahmad,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Re(I) complex, [Re(PyPzH)(CO)3Cl] where PyPzH = 2-(1H-pyrazol-3-yl)pyridine, was successfully synthesised and characterised with an infrared (IR), ultraviolet-visible (UV-Vis), 1H and 13C nuclear magnetic resonance (NMR) spectroscopies and X-ray crystallography. The IR spectrum featured three n(C≡O), n(N-H), n(C=N) and n(C=C) signals at (1860-2020), 3137, 1614 and 1513 cm-1, respectively. The UV-Vis spectrum of the complex exhibited ligand-centred (π®>*) electronic excitations [λmax = 227 nm, ε = 1.942 x 104 M-1cm-1; lmax = 292 nm, ε = 0.853 x 104 M-1cm-1] and a metal-to-ligand charge transfer (MLCT) band [lmax = 331 nm, ε = 0.467 x 104 M-1cm-1]. The 13C and 1H-NMR spectra exhibited the characteristic signals of the three C≡O (189.0 – 199.0 ppm) and NH (14.84 ppm), respectively. The X-ray structure of [Re(PyPzH)(CO)3Cl] showed the crystal adopted a monoclinic system with a C2/c space group [unit cell dimensions: a = 27.7422(14) Å, b = 11.1456(5) Å, c = 9.2461(4) Å with α = γ = 90º and β = 92.552(2)º]. Density functional theory (DFT) and time-dependent (TD) DFT calculations were performed to investigate the optimised structural geometry and electronic properties of the title complex. The results showed that the highest-occupied molecular orbital (HOMO) was predominantly found on the dπ-orbitals of Re(I), Cl and CO. While the lowest-unoccupied molecular orbital (LUMO) was located on the PyPzH moiety. The structural and photophysical properties of the [Re(PyPzH)(CO)3Cl] were established and the reaction enthalpies for the dissociation of Cl atom in the formation of [Re(PyPzH)(CO)3]• were discussed in view of its potential application for photocatalytic CO2 reduction.